Oriented ice eddy detection network based on the Sentinel-1 dual-polarization data - Jinqun Wu; Jinqun Wu; Yiqin Zheng; Tingting Wang; Chunyong Ma; Chunyong Ma; Ge Chen; Ge Chen (Frontiers in Marine Science)
The complex convergence of cold and warm ocean currents in the Nordic Seas provides suitable conditions for the formation and development of eddies. In the Marginal Ice Zones (MIZs), ice eddies contribute to the accelerated melting of surface sea ice by facilitating vertical heat transfer, which influences the evolution of the marginal ice zone and plays an indirect role in regulating global climate. In this paper, we employed high-resolution synthetic aperture radar (SAR) satellite imagery and proposed an oriented ice eddy detection network (OIEDNet) framework to conduct automated detection and spatiotemporal analysis of ice eddies in the Nordic Seas. Firstly, a high-quality RGB false-color imaging method was developed based on Sentinel-1 dual-polarization (HH+HV) Extra-Wide Swath (EW) mode products, effectively integrating denoising algorithms and image processing techniques. Secondly, an automatic ice eddy detection method based on oriented bounding boxes (OBB) was constructed to identify the ice eddy and output features such as horizontal scales, eddy centers and rotation angles. Finally, the characteristics of the detected ice eddies in the Nordic Seas during 2022-2023 were systematically analyzed. The results demonstrate that the proposed OIEDNet exhibits significant performance in ice eddy detection.